Information systems project abandonment: A stakeholder analysis - PAN, Gary Shan Chi (Institutional Knowledge at Singapore Management University, 2005)
This case study reports on the experience of an organization in Singapore in implementing and eventually abandoning an electronic procurement project. By means of a stakeholder analysis, it examines stakeholders’ roles in the organization's decision to abandon the software project. This study uses Freeman's stakeholder analytical framework (Freeman, R. (1984). Strategic management: a stakeholder approach. Massachusetts: Pitman) to interpret data and develop four major findings. By providing a better understanding of project stakeholders’ perceptions, expectations and interrelationships during project development, this study presents researchers with a project abandonment evaluation framework that is enhanced with a stakeholder perspective. The lessons learned from the case analysis can also offer practitioners useful insights on how to manage stakeholders in information systems development projects.